The concept of Islamic education reform KH. Ahmad Dahlan and its implementation in modern Islamic education - Marlini, Linda; Fakhrurazi; Shofiyah, Siti (UIN Salatiga, 2024)
This study aims to determine the concept of Islamic education reform of KH. Ahmad Dahlan and its implementation in modern Islamic education. This research uses concept analysis from various works of K.H. Ahmad Dahlan and materials that become primary sources and secondary sources in various studies, then connected and analyzed through the content analysis process. This research has concluded that KH. Ahmad Dahlan's efforts to renew Islamic education were carried out among others by uniting traditional-based education systems and modern education systems, collaborating religious sciences and general sciences, and integrating Islamic religious education and general education which includes aspects of curriculum, methods and institutions. KH. Ahmad Dahlan also put forward five concepts, namely pragmatic, progressive, pedagogical, social which were applied in the Muhammadiyah organization. This research can be a scientific treasure in the treasures of Islamic education reform